Citrus Canopy Health Is Highly Important for HLB Tolerance - Levy, Amit; Vashisth, Tripti (EDIS, 2022)
In this article, we will show evidence that HLB infected trees with a healthy canopy produce higher fruit yields. Surprisingly, we didn’t find that to be true for trees with higher Ct values. Prime attention should be paid to keeping canopy healthy, rather than reducing bacteria titers